Efeitos supressivos da apresentação contingente e não contingente do jato de ar quente em Rattus norvegicus - GASPAR, Christian Diego de França (Universidade Federal do Pará, 2019)
Thus, the objective of this work was to verify the suppressive effects of the contingent and noncontingent presentation of hot air blast (HAB), if tested in situations like those required to produce this effect with electric shock. After the pressure training the bar phase and the identification of the baseline, six rats were divided into two groups with three animals each. The groups were exposed to twenty sessions in each phase (baseline, test phase and reconditioning), but for the Punishment Group (PUN) the HAB was administered in a contingent manner by pressing the bar in a joint scheme of VI 30s punishment + VI 30s reinforcement, while for the Yoked Group (ACO) the HAB occurred in a non-contingent manner, due to the occurrence in the Punishment Group, superimposed on a reinforcement scheme (VI 30s). In the end of the experiment, the percentage suppression index was 73% for PUN group and 49% for ACO group. The identified differential suppression was the missing element to legitimize HAB as a punitive stimulus capable of suppressing previously established responses and of testing the generality of aversive events with electric shock in basic experimental procedures.